PRINCIPLES OF INTENSIVE CARE OF BRAIN DEATH DONOR - S. K. Sergienko; O. N. Reznik; A. A. Pustovalov; I. V. Loginov (Вестник трансплантологии и искусственных органов)
Successful donor’s programs have to base on the fundamental knowledge about brain death and principles of do- nor intensive care. In this article there is presented a comprehensive review of modern literature which highlights the main issues in donor care management.